2019
DOI: 10.1111/iwj.13127
|View full text |Cite
|
Sign up to set email alerts
|

The role of reconstructive microsurgery in treating lower‐extremity chronic wounds

Abstract: Frequently considered chronic wounds for reconstruction are wounds lacking healing progress despite good wound care. And those needing microsurgical reconstruction are chronic wounds that are unable to close by local flap or skin grafts, wounds with exposed vital structure such as tendon and bones, and wounds that have prolonged infections such as osteomyelitis and skin necrosis. The reconstruction for soft tissue defects not only aims to provide coverage but to restore function and acceptable form as well. Wo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 15 publications
(5 citation statements)
references
References 52 publications
0
4
0
1
Order By: Relevance
“…Previously conducted in vitro experiments showed no difference in terms of pro-angiogenic factor composition between HPS obtained from diabetic patients or patients receiving anticoagulants and HPS obtained from healthy blood donors [ 22 ]. This is promising for the clinical translation of this approach in this patient group, that is burdened by chronic leg ulcers, commonly necessitating partial or complete lower extremity amputation and complex reconstructive surgery [ 55 ]. Beyond reducing overall morbidity and the length of patient hospitalization, HPS holds, therefore, the potential to reduce the large healthcare costs associated with these conditions.…”
Section: Discussionmentioning
confidence: 99%
“…Previously conducted in vitro experiments showed no difference in terms of pro-angiogenic factor composition between HPS obtained from diabetic patients or patients receiving anticoagulants and HPS obtained from healthy blood donors [ 22 ]. This is promising for the clinical translation of this approach in this patient group, that is burdened by chronic leg ulcers, commonly necessitating partial or complete lower extremity amputation and complex reconstructive surgery [ 55 ]. Beyond reducing overall morbidity and the length of patient hospitalization, HPS holds, therefore, the potential to reduce the large healthcare costs associated with these conditions.…”
Section: Discussionmentioning
confidence: 99%
“…Promotion of neovascularization by ECM material ( 16) may assist in establishment of blood supply from both the flap and the underlying tissues of the defect. Increasing the local blood supply to the defect through vascularization also minimizes risk of infection via increased perfusion of protective immune system elements and/or systemically administered antibiotics (25). Indeed, proper site preparation is vital for successful closure of chronic defects with positive post-debridement cultures being a proven predictor of failure of flap closure ( 26), as such our procedure included aggressive debridement and removal of chronic defective tissues.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies reported the e cacy of using free tissue transfer in treatment of chronic osteomyelitis. [5][6][7][8][9][10] Free aps regardless of the composition provide reliable tissues not only to cover large defects but also to obliterate dead space, without further compromising local tissue. [2,11] In this study, the authors aimed to evaluate the in uence of co-morbidities and other factors such as diabetic foot ulcers, ap types, using antibiotic-beads and NPWT on the outcome of osteomyelitis treated with free aps.…”
Section: Discussionmentioning
confidence: 99%